Biodiversity and carbon stock analysis in the high conservation value forest within the oil palm plantation setting in Central Kalimantan, Indonesia - SITI MAIMUNAH; YOVI AVIANTO; AMIR NOVIYANTO; FADHLULLAH RAMADHANI; VALENSI KAUTSAR; YOHANA THERESIA MARIA ASTUTI; SRI GUNAWAN; JH SAMEK (Society for Indonesian Biodiversity, 2026)
Abstract. Maimunah S, Avianto Y, Noviyanto A, Ramadhani F, Kautsar V, Astuti YTM, Gunawan S, Samek J. 2026. Biodiversity and carbon stock analysis in the high conservation value forest within the oil palm plantation setting in Central Kalimantan, Indonesia. Biodiversitas 27 (4): d270408. https://doi.org/10.13057/biodiv/d270408. High Conservation Value Forests (HCVFs) within oil palm landscapes play a crucial role in maintaining biodiversity and ecosystem services, including carbon storage. However, empirical evidence quantifying biodiversity-carbon co-benefits in industrial plantation contexts remains limited in Indonesia. This study assessed plant biodiversity, wildlife presence, and aboveground carbon stock in a 65-ha HCVF managed by a private enterprise in Kotawaringin Timur, Central Kalimantan, Indonesia. Field surveys were conducted using an 8% sampling intensity across 13 nested plots (50 m × 80 m). Tree and seedling diversity were evaluated using Margalef, Menhinick, Shannon-Wiener, Simpson, and evenness indices. Carbon stock was estimated based on diameter and height measurements using the USAID-MSU Biodiversity and Carbon Potential Calculator. Wildlife presence was documented through direct and indirect field evidence. A total of 68 tree species and 26 seedling species were recorded. Shannon diversity indices indicated high diversity at the tree level (H′ = 3.31) and moderate diversity at the seedling level (H′ = 2.41), with high species evenness (E>0.70). The forest was dominated by secondary Dipterocarp species. Average aboveground carbon stock reached 191.44 tC ha⁻¹, corresponding to a total carbon reserve of 12,443.72 tC across the HCVF area. Several protected wildlife fauna, including hornbills, pangolins, and gibbons, were identified. These findings demonstrate that HCVFs embedded within oil palm concessions can simultaneously support biodiversity conservation and climate mitigation. Effective protection of such areas is therefore essential for strengthening sustainability performance and achieving conservation commitments in tropical agricultural landscapes.